EXPRESSION OF NeuGc ON PIG CORNEAS AND ITS POTENTIAL SIGNIFICANCE IN PIG CORNEAL XENOTRANSPLANTATION - Lee, Whayoung (Cornea, 2016)
PURPOSE: Pigs expressing neither galactose-α1,3-galactose (Gal) nor N-glycolylneuraminic acid (NeuGc) take xenotransplantation one step closer to the clinic. Our aims were (i) to document the lack of NeuGc expression on corneas and aortas, and cultured endothelial cells (aortic [AECs]; corneal [CECs]) of GTKO/NeuGcKO pigs, and (ii) to investigate whether the absence of NeuGc reduced human antibody binding to the tissues and cells. METHODS: Wild-type (WT), GTKO, and GTKO/NeuGcKO pig were used for the study. Human tissues and cultured cells were negative controls. Immunofluorescence staining was performed using anti-Gal and anti-NeuGc antibodies, and to determine human IgM and IgG binding to tissues. Flow cytometric analysis was used to determine Gal and NeuGc expression on cultured CECs and AECs and to measure human IgM/IgG binding to these cells. RESULTS: Both Gal and NeuGc were detected on WT pig corneas and aortas. Although GTKO pigs expressed NeuGc, neither human nor GTKO/NeuGcKO pigs expressed Gal or NeuGc. Human IgM/IgG binding to corneas and aortas from GTKO and GTKO/NeuGcKO pigs was reduced compared to binding to WT pigs. Human antibody binding to GTKO/NeuGcKO AECs was significantly less than to GTKO AECs, but there was no significant difference in binding between GTKO and GTKO/NeuGcKO CECs. CONCLUSIONS: The absence of NeuGc on GTKO aortic tissue and AECs is associated with reduced human antibody binding, and possibly will provide better outcome in clinical xenotransplantation using vascularized organs. For clinical corneal xenotransplantation, the absence of NeuGc expression on GTKO/NeuGcKO pig corneas may not prove an advantage over GTKO corneas.